Recovering nutrients and rejecting trace organic compounds in human urine by a forward osmosis–membrane distillation (FO–MD) hybrid system - Chihiro Gau; Satoshi Sato; Daizhou Zhang; Yasuhiro Ishibashi; Jun Kobayashi (Water Science and Technology, 2022)
Urine is a major source of reclaimed water and fertilizer. Urine treatment involves two key processes: the recovery of nutrients and the rejection of trace organic compounds (TOrCs). In this study, we investigated the rejection of TOrCs and the recovery of nutrients in human urine using a seawater-driven forward osmosis and membrane distillation (FO–MD) hybrid system. Three 24 h experiments were conducted at draw solution temperatures of 30, 40, and 50 °C. The average rejection rates of cations, anions, and dissolved organic carbon were more than 93.7% and 79.5% in the FO–MD system and FO side, respectively. Ten types of TOrCs were detected in the feed solution, whereas none were detected in the product water, indicating that the TOrCs were completely rejected. The precipitates, i.e., the recovered nutrients in the FO side, were extremely close to magnesium ammonium phosphate (struvite, MgNH4PO4·6H2O), according to their electron microscopic images, elemental composition, and X-ray diffraction spectra, and it was estimated that approximately 85% of the nutrients in the feed solution were recovered. The rejection and recovery efficiencies were unaffected by the draw solution temperature. These results indicate the potential for the sustainable use of FO–MD-based treatments for human urine. HIGHLIGHTS More than 93.7% of cations and anions in feed solution were rejected.; Trace organic compounds were completely rejected in this system.; Nutrients in feed solution were recovered as struvite.;